Job Involvement and Organizational Commitment of Employees of Prehospital Emergency Medical System - Rahati; Sotudeh-Arani; Adib-Hajbaghery; Rostami (Kashan University of Medical Sciences, 2015)
Background Several studies are available on organizational commitment of employees in different organizations. However, the organizational commitment and job involvement of the employees in the prehospital emergency medical system (PEMS) of Iran have largely been ignored. Objectives This study aimed to investigate the organizational commitment and job involvement of the employees of PEMS and the relationship between these two issues. Materials and Methods This cross-sectional study was conducted on 160 employees of Kashan PEMS who were selected through a census method in 2014. A 3-part instrument was used in this study, including a demographic questionnaire, the Allen and Miller's organizational commitment inventory, and the Lodahl and Kejner's job involvement inventory. We used descriptive statistics, Spearman correlation coefficient, Kruskal-Wallis, Friedman, analysis of variance, and Tukey post hoc tests to analyze the data. Results The mean job involvement and organizational commitment scores were 61.78 ± 10.69 and 73.89 ± 13.58, respectively. The mean scores of job involvement and organizational commitment were significantly different in subjects with different work experiences (P = 0.043 and P = 0.012, respectively). However, no significant differences were observed between the mean scores of organizational commitment and job involvement in subjects with different fields of study, different levels of interest in the profession, and various educational levels. A direct significant correlation was found between the total scores of organizational commitment and job involvement of workers in Kashan PEMS (r = 0.910, P < 0.001). Conclusions This study showed that the employees in the Kashan PEMS obtained half of the score of organizational commitment and about two-thirds of the job involvement score. Therefore, the higher level managers of the emergency medical system are advised to implement some strategies to increase the employees' job involvement and organizational commitment.